Duas novas espécies de Megacoelium Szidat, 1954 (Trematoda: Heploporidae), parasitas estomacais de peixes da Amazônia Brasileira, com uma redefinição do gênero - Thatcher, Vernon Everet; Varella, Angela M. B (Acta Amazonica, 1981)
Megacoelium Szidat, 1954 (Trematoda Haploporidae), a stomach parasite of South American loricariid catfish, was redefined. This genus was found to have cuticular spines within the suckers and a hermaphroditic cirrus. Two new species were described in the genus, namely: M. spinispecum n. sp. from Pterygoplichthys sp. and M. spinicavum n. sp. from Pterygoplichthys pardalis (Castelnau). The new species differ from the type (M. plecostomi Szidat, 1954) in being much larger and in having larger suckers and a non-sinuous testis. M. spinispecum is larger than M. spinicavum and has smaller suckers and a smaller hermaphroditic sac. M. spinispecum also has a prominent receptaculum seminis uterinum which the other species lacks.